Exogenous fibrolytic enzymes affect the nutritive value and the performance of Nellore bulls when added to corn-based silages - Salvo, Pedro Augusto Ribeiro (2019)
The use of silages made from corn crop is common in Brazil and around the world. The high moisture corn and the whole-plant corn silage are largely used by farmers in feedlot diets. Another silage made from the corn, which seems to have great potential, is the snaplage. The snaplage is composed by the ear of the corn, which contains husk, cob, and grains. Animals fed diets with high moisture corn silages have better feed efficiency, due to the increase of starch digestibility. This increase is dependent on three factors: length of storage, grain particle size, and moisture. The improvement in starch digestibility occurs because of endosperm protein matrix solubilization. However, another barrier that can impair the grain nutrients availability, such as, starch, is the endosperm cell wall. The cell wall is composed mainly by arabinoxylans. Therefore, the application of exogenous fibrolytic enzymes can enhance the availability of the nutrients, by the solubilization of cell wall components. The optimal pH and temperature of the silages might be beneficial for the enzymes to act. The objective of the first study was to evaluate the performance of Nellore bulls fed diets with high moisture corn and snaplage, with or without the addition of exogenous fibrolytic enzymes at ensiling. In the second study, the objective was to evaluate the chemical composition, the nutrient digestibility, and the fermentative profile of whole-plant corn silages added different doses of fibrolytic enzymes, ensiled for different times of storage. As a result of the first study, the bulls fed diets with silages treated with fibrolytic enzymes showed a decreased dry matter intake and an increased feed efficiency. The enzyme treatment decreased the NDF content and increased the DM in vitro and in situ digestibility of the high moisture corn silage. Moreover, the acetic acid and ethyl acetate concentration was increased for the high moisture corn treated with the enzymes. There was no difference between the diets. In the second study with whole-plant corn silage, the exogenous fibrolytic enzymes addition increased the acetic acid concentration and decreased the concentrations of ethanol, ethyl lactate, and ethyl acetate. In conclusion, the addition of exogenous fibrolytic enzymes in high moisture corn silages improved the animal performance, and in whole-plant corn silages, it affected the fermentative profile.